Analisis Isi Diskriminasi Gender Pada Budaya Keluarga Batak Dalam Film Ngeri-Ngeri Sedap - Hutahaean, Teresa Cyndyana Novianti; Fitria Widiyani Roosinda; Ariyan Alfraita (CV. Ulil Albab Corp, 2025)
This research aims to analyze the representation of gender discrimination in the film Ngeri-Ngeri Sedap using a content analysis method based on John Fiske's theory with a quantitative approach. Gender discrimination is a complex social phenomenon, encompassing various forms of inequality based on sex. In the Indonesian context, gender discrimination is still widespread, especially due to a long-rooted patriarchal culture, as depicted in the film Ngeri-Ngeri Sedap. This film, which highlights Batak family culture, reflects various forms of gender discrimination, including subordination, marginalization, stereotypes and violence. The results showed that of the total of 16 scenes analyzed, the subordination category had the highest percentage at 50% with a frequency of 8 scenes, followed by stereotypes (31%), and marginalization (19%). The category of violence is not found in this film. This research concludes that the most prominent gender discrimination in Ngeri-Ngeri Sedap is subordination, which describes women's position as subordinates in Batak family culture. It is hoped that these results will provide a deeper understanding of how the media, especially films, represent and influence social perceptions regarding gender discrimination.